Net Profit Margin Sebagai Moderator Tax Planning dan Corporate Social Responsibility pada Manajemen Laba - Adibah Yahya; Rina Nurjanah; Lisa Kustina (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the effect of Tax Planning, Corporate Social Responsibility (CSR) and Net Profit Margin (NPM) as a moderating variable on Profit Management. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. This type of research is quantitative research, the population in this study are consumer goods manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2020, with a sample of 33 companies. The type of data in this research is quantitative data. Technique analysis in this research uses multiple linear regression and Moderated Regression Analysis (MRA). The test results show that Tax Planning positively affects earnings management, while Corporate Social Responsibility has a negative effect on earnings management. The MRA test results show that NPM cannot be used as a moderating variable between tax planning and CSR on earnings management.Keywords: earnings management, corporate social responsibility net profit margin, tax planning